Genetic variability of Myxobolus nagaraensis (Bivalvulida: Myxobolidae) infecting freshwater gobies Rhinogobius Gill 1859 (Gobiiformes: Oxudercidae) from rivers in Japan - Kana Kurusu; Naoyuki Hioki; Mizuho Shima; Sunao Kawakami; Yuta Hasebe; Noriyuki Takai; Jun Matsumoto; Aya Masuda (International Journal for Parasitology: Parasites and Wildlife)
Myxobolus nagaraensis is a myxozoan parasite first reported in freshwater gobies (Rhinogobius spp.) from the Nagara River, Gifu Prefecture, Japan. Myxospores of M. nagaraensis form plasmodia in the visceral cavities of gobies, commonly presenting as distended abdomens. Although Rhinogobius is a common fish genus in Japan, details of M. nagaraensis, including genetic information, remain unknown. We compared the nucleotide sequences of the ribosomal RNA gene (rDNA) of M. nagaraensis from three different host species (R. fluviatilis, R. nagoyae, and R. similis) caught in three different rivers in Japan (Sakai, Sagami, and Kaname). The ITS region (ITS-1, 5.8S rDNA, and ITS-2) and large subunit (LSU) rDNA exhibited 49 and 55 variable sites, respectively. The highest nucleotide diversity was observed in the ITS region (0.00962), whereas that of the LSU rDNA was 0.00187. Differences in host species, rather than rivers, were a significant factor for genetic variation in both the ITS region (62.58%; P < 0.001) and LSU rDNA (55.22%; P < 0.01). Significant genetic variation was observed in M. nagaraensis from R. similis compared to R. fluviatilis (P < 0.001) or R. nagoyae (P < 0.001) from the same river. Such details are valuable for understanding parasite dispersal and its ecological impact on Rhinogobius hosts.